Sight [videorecording (DVD)] - Hyatt, Andrew, 1982-; Duigan, John, 1949-; McLaughlin, Buzz, 1944-; Chen, Terry; Kinnear, Greg, 1963-; Wang, Danni (Actress); Ma, Raymond; Wang, Ben (Actor); Zhang, Jayden; Ho, Wai Ching; Flanagan, Fionnula, 1941- (Angel Studios, 2024)
"Sight, starring Greg Kinnear and Terry Chen, follows the inspiring true story of Ming Wang, an impoverished Chinese prodigy who flees Communist China to become a pioneering eye surgoen in America. When tasked with restoring the sight of an orphan who was blinded by her step mother, he must confront the trauma of living through a violent uprising in his youth, the Cultural Revolution."--Container.